The Origin and Significance of the Twenty-Four Solar Terms in China - Xu Wangsheng (Contemporary Social Sciences, 2017)
The “Twenty-Four Solar Terms” is an integrated knowledge system and functional social practice initiated and developed by ancient Chinese. Appling to their daily lives and agricultural production, based on records of the periodic motions of the sun, this knowledge system echoes seasonal and climate changes, phenological variation and reflects the features of ancient agricultural activities. As a comprehensive demonstration of their lives and production, it is a phenomenal achievement thanks to the ancient Chinese people’s experience and wisdom. The “Twenty-Four Solar Terms” is also a cultural phenomenon unique to China, geographic location, the Yellow River Basin being at a mid-latitude zone with distinctive seasonal climate changes; its long-existing agrarian tradition, advanced agricultural philosophy and a harmonious lifestyle. In the meantime, while China’s superior knowledge on astronomy made its formation technically possible, the “agriculture first” governmental policy and the “prefectures and counties” administrative system, introduced by governors from Qin and Han Dynasties, cultivated its formation institutionally. Besides, the “Twenty-Four Solar Terms” is the outcome of the harmonious civilization progress and traditional Chinese culture, which is different from Western Europe’s aggressive and predatory industrial expansion. The “Twenty-Four Solar Terms” is still of great cultural and practical significance in China even today. It highlights the “unity of mankind and nature” philosophy and serves as another signature symbol of the Chinese culture. While China is more and more engaging in international affairs, the “Twenty-Four Solar Terms” facilitates the rest of the world to understand China from another angle